Adult congenital heart disease and the COVID-19 pandemic. Issue 17 (10th June 2020) - Radke, Robert M; Frenzel, Tim; Baumgartner, Helmut; Diller, Gerhard-Paul
Abstract : Adults with congenital heart disease (ACHD) may be at high risk in the case of COVID-19. Due to the heterogeneity of ACHD and secondary complications, risk profiles are, however, not uniform. This document aims to give an overview of relevant data and outline our pragmatic approach to disease prevention and management. Based on anatomy and additional physiological factors including symptoms, exercise capacity, heart failure, pulmonary hypertension and cyanosis, we propose a pragmatic approach to categorising patients into low-risk, intermediate-risk and high-risk groups. We regard especially patients with complex cyanotic conditions, those with palliated univentricular hearts, heart failure, severe valvular disease or pulmonary hypertension as high-risk patients. To avoid infection, we recommend self-isolation and exemption from work for these cohorts. Infected ACHD patients with low or moderate risk and without signs of deterioration may be remotely followed and cared for at home while in self isolation. High-risk patients or those with signs of respiratory or cardiovascular impairment require admission ideally at a tertiary ACHD centre. Especially patients with complex, cyanotic disease, heart failure and arrhythmias require particular attention. Treatment in patients with cyanotic heart disease should be guided by the relative degree of desaturation compared with baseline and lactate levels rather than absolute oxygen saturation levels. Patients with right heart dilatation or dysfunction are potentially at increased risk of right heart failure as mechanical ventilation and acute respiratory distress syndrome can lead to increase in pulmonary arterial pressures.